Effectiveness of a school-based physical activity-related injury prevention program on risk behavior and neuromotor fitness a cluster randomized controlled trial - Bakker Ingrid; Verhagen Evert ALM; Chinapaw Mai JM; Collard Dorine CM; van Mechelen Willem (BMC, 2010)
Abstract Background To investigate the effects of a school-based physical activity-related injury prevention program, called 'iPlay', on risk behavior and neuromotor fitness. Methods In this cluster randomized controlled trial 40 primary schools throughout the Netherlands were randomly assigned in an intervention (n = 20) or control group (n = 20). The study includes 2,210 children aged 10-12 years. The iPlay-intervention takes one school year and consists of a teacher manual, informative newsletters and posters, a website, and simple exercises to be carried out during physical education classes. Outcomes measures were self-reported injury preventing behavior, self-reported behavioral determinants (knowledge, attitude, social-influence, self-efficacy, and intention), and neuromotor fitness. Results The iPlay-program was not able to significantly improve injury-preventing behavior. The program did significantly improve knowledge and attitude, two determinants of behavior. The effect of the intervention-program on behavior appeared to be significantly mediated by knowledge and attitude. Improved scores on attitude, social norm, self-efficacy and intention were significantly related to changes in injury preventing behavior. Furthermore, iPlay resulted in small non-significant improvements in neuromotor fitness in favor of the intervention group. Conclusion This cluster randomized controlled trial showed that the iPlay-program did significantly improved behavioral determinants. However, this effect on knowledge and attitude was not strong enough to improve injury preventing behavior. Furthermore, the results confirm the hypothetical model that injury preventing behavior is determined by intention, attitude, social norm and self-efficacy. Trial number ISRCTN78846684